IMPACT OF ERGONOMIC FACTORS ON UNIVERSITY STUDENTS’ ACADEMIC PERFORMANCE - Iram Bashir; Dr Nasrullah Khan; Tahira Tariq (International Journal of Contemporary Issues in Social Sciences, 2024)
Ergonomics significantly influences university students’ academic performance. This research aimed to explore the impact of ergonomic factors on students’ performance, focusing on physical, cognitive, and macro-level factors. Data were gathered through a structured questionnaire from 318 social sciences students across universities, using a 24-items Likert scale. The study revealed a significant relationship between ergonomic factors and academic performance. Regression analysis showed how workplace design, lighting, temperature, and noise affected students, alongside cognitive factors like learning styles and macro factors such as access to technology. Recommendations include improving classroom design, incorporating diverse teaching methods, and enhancing learning environments.